Identifikasi Spesies Lokal Hasil Hutan Bukan Kayu (HHBK) Dan Potensi Pemanfaatannya Pada Ekosistem Gambut Di Kabupaten Pulang Pisau: Identification of Local Non-Timber Forest Product (HHBK) Species and Their Utilization Potential in the Peatland Ecosystems of Pulang Pisau Regency - Lia, Kamaliah; S, Annisa; Ramadhani, Dinda T.; Tamara, Dhea; Sabira, Nayara I. (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2025)
Pulang Pisau Regency in Central Kalimantan is known for its extensive peatland ecosystems, which are rich in biodiversity. Peat ecosystems function not only as major carbon sinks but also as habitats for various local non-timber forest product (NTFP) species that have long supported the socio-economic livelihoods of local communities. This study was conducted to identify local NTFP species that grow within the peatland ecosystems of Pulang Pisau and to assess their ecological and economic utilization potential. Through field surveys, vegetation inventories, and interviews with Indigenous communities and local artisans, the research identified several key species such as swamp jelutung (Dyera polyphylla), purun (Eleocharis dulcis), rattan (Calamus spp.), tengang (Shorea balangeran), various medicinal plants, forest honey, and peat swamp food plants. Each species offers diverse utilization prospects, ranging from handicraft industries and traditional medicine to local food resources and peatland restoration efforts. These findings indicate that NTFPs hold strategic potential as a foundation for a green economy and as a contributor to the sustainability of peatland ecosystems in Pulang Pisau Regency. Keywords: HHBK, Peatland Ecosystem, Pulang Pisau, Local Species, Peatland Restoration